Proton Conductors based on Metal Phosphonate Hybrid Materials for PEM Fuel Cells - Cabeza-Díaz, Aurelio; Pérez-Colodrero, Rosario Mercedes; Bazaga-García, Montse; Hernández Alonso, Daniel; Compaña Prieto, José Manuel; Olivera-Pastor, Pascual; Losilla, Enrique R.; García-Aranda, Miguel Ángel; León-Reina, Laura (My University, 2014)
The necessity of energy and power generation is constantly growing. Fossils fuels are quickly becoming unsatisfactory substrates due to both their emission of pollutants and their finite expectancy. Fuel cells are one of the best alternatives as they are clean, durable, and highly efficient 1. MOFs will be attractive candidates for this application because of their tuneable pore size functionality as well as their chemical and thermal stability and presence of acidic protons within their structure2. In the present work, we report the syntheses, crystal structural and proton conductivities of various metal phosphonate derivatives, using both rigid (5-(dihydroxyphosphoryl)isophthalic acid, PiPhtA and 2-hydroxyphosphonoacetic acid, HPAA) and flexible (hexa- or octamethylenediamine-N,N,N′,N′-tetrakis-(methylenephosphonic acid, H8HDTMP or H8ODTMP) multifunctional ligands. These materials show 3D open-frameworks containing 1D channels decorated with phosphonic and carboxylic acid groups and filled with hydrogen bonded water molecules what make them good candidates as proton conductors. For instance, Ca-PiPhtA, containing a rigid ligand, exhibits a proton conductivity of 5.7•10-4 S/cm which increases to 6.6•10-3 S/cm when the sample is exposed to ammonia vapors3. Other magnesium or lanthanides metal phosphonates, built with flexible ligands, show conductivities values range between 1.6 10-3 S/cm (for MgODTMP4) and 8.6 10-3 S/cm (for LaHDTMP5) at T=292K at ~100% relative humidity, and activation energies values typically attributed to a Grotthuss mechanism.
Keywords: Conductividad eléctrica; MOFs; Fuel Cells; Proton conductivity; Hybrid materials; Metal phosphonates